O potencial das células intestinais como fonte de células progenitoras pancreáticas - Glanzner, Werner Giehl (2012)
The objective of the present study was to establish a primary culture of intestinal cells and to characterize the mRNA expression profile of genes related to pancreatic formation, development and insulin metabolism. The mRNA expression of pancreatic-related genes was evaluated in intestinal tissue and isolated cells from newborn piglet by qRT-PCR. The tissue and isolated cells before and after culture from the first two passages were evaluated for Pdx1 (Pancreatic and duodenal homeobox), Ngn3 (Neurogin3), NeuroD1 (Neurogenic differentiation 1), PC1/3 (Prohormone convertase 1/3), PC2 (Prohormone convertase 2) and insulin (INS) gene expression. The intestinal tissue and passage 2 of cultured cells were evaluated for the presence of insulin by immunofluorescence. In the first experiment, cells were cultured in RPMI medium plus EGF, penicillin, amphotericin B, and insulin (10 μg/ml). The Ngn3, PC1/3 and PC2 expression did not differ during cell isolation process and culture passages, while for genes Pdx1, INS and NeuroD1 the expression decreased in cultured cells. In the second experiment, a primary cell culture of porcine newborn intestinal cells were performed using the same medium describe above but without insulin (control group) or with glucose (25 mM) and without insulin (treatment group). The objective of this experiment was to evaluate the mRNA expression of pancreatic-related genes in response to glucose. Independently of the presence of glucose, the expression of all studied genes decreased at passage 1 and raised (to the same levels found in intestine) or even higher (NeuroD1) at passage 2 of cultured cells, except for Pdx1. The Pdx1 mRNA expression observed in intestinal tissue was maintained through first cell passage, but decreased at passage 2. The intestinal tissue and cells cultured with or without glucose from the second passage did not reveal any insulin-producing cell by immunofluorescence. Our results let us to conclude that newborn duodenal tissue had cells that express mRNA pancreatic markers; however, these cells were not able to produce insulin. The results of this study allowed us to infer that newborn piglet duodenal cells have potential to be transdifferentiated in insulin producing cells for cell therapy of type 1 diabetes mellitus.